Impact of affordable housing construction and housing and communal services on the welfare of the population by typical projects - SHODMONOVNA, FAYZIYEVA SHIRIN zx (The journal of contemporary issues in business and government, 2021)
The article describes the activities of housing and communal services, the types of services, reforms to improve the efficiency of housing and communal services, the ongoing reforms to improve the efficiency of utilities and the solution of the problem of employment.